Teaching and learning in Geography: Cartography and Remote Sensing as didactic and technological resources for Elementary School (Research, Society and Development, 2023)
The research addressed Cartography and Remote Sensing as didactic and technological resources in elementary education, aimed at teaching and learning in Geography. The objective of the work was to analyze Cartography and Remote Sensing as didactic resources for teaching and learning in Geography in Elementary School. The methodological construction used exploratory research as to the objectives, using a bibliographic research procedure of subjects related to Cartography, Geoprocessing, and Geography. It was concluded that geotechnologies present in computers and especially in cell phones are relevant for students to understand their locations and spatial dynamics in the city, contributing to the applicability of concepts of geographic science.